ANALYSIS OF THE EFFECT OF INFRASTRUCTURE ON THE LAND VALUE IN URBAN AREAS - Mahlan Zuhdi Hanan (NIM : 15113065), Muhammad
A land is one of the non-renewable resources that has increasing value along the time as the demand continues to grow. In the developing urban area, the land value increases faster than in other areas. Land value is become important to be calculated accurately, because of its role as a reference for the government to set the taxes as its regional income. This study is intended to find the influence of existing infrastructure to the land’s value and determine its mathematical model. Land’s value model is determined by using multivariate linear regression analysis with land’s value as its dependent variable and distance from existing infrastructure as its independent variable. Statistical parameters obtained from the regression analysis process is tested with the t test, F test, and R2 to choose the best representative model. This study shows that distance from the university, medical facility, and main road are significance infrastructure which is influencing the land’s value in Bandung. In the end, the predicted land’s value calculated from chosen model shows low similarity compared to the actual land’s value based on a high root mean squared error (RMSE) value.